2018
DOI: 10.3389/fphys.2018.00856
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Contractile Function Declines With Age in Skeletal Muscle Feed Arteries

Abstract: Aging induces a progressive decline in vasoconstrictor responses in central and peripheral arteries. This study investigated the hypothesis that vascular smooth muscle (VSM) contractile function declines with age in soleus muscle feed arteries (SFA). Contractile function of cannulated SFA isolated from young (4 months) and old (24 months) Fischer 344 rats was assessed by measuring constrictor responses of denuded (endothelium removed) SFA to norepinephrine (NE), phenylephrine (PE), and angiotensin II (Ang II).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 65 publications
(81 reference statements)
6
41
0
Order By: Relevance
“…However, ECM deformation was used to assess the vasoconstrictor response and given that aged arteries are stiffer than their younger counterparts, VSMC actomyosin activity may remain intact [97] . In agreement with this, cell-matrix adhesions were subjected to increased mechanical load in aged arteries, compared to their younger counterparts [96] . Further investigation is now required to assess whether the mechanisms of VSMC actomyosin signaling is influenced by matrix stiffness.…”
Section: Cvd and The Role Of Matrix Stiffnesssupporting
confidence: 64%
See 3 more Smart Citations
“…However, ECM deformation was used to assess the vasoconstrictor response and given that aged arteries are stiffer than their younger counterparts, VSMC actomyosin activity may remain intact [97] . In agreement with this, cell-matrix adhesions were subjected to increased mechanical load in aged arteries, compared to their younger counterparts [96] . Further investigation is now required to assess whether the mechanisms of VSMC actomyosin signaling is influenced by matrix stiffness.…”
Section: Cvd and The Role Of Matrix Stiffnesssupporting
confidence: 64%
“…For example, a recent study investigated the ex-vivo vasoconstrictor response of young and old soleus muscle feed arteries. Despite an upregulation of ROCK activity, there was a decreased constrictor response in the aged vessels [96] . Aged VSMCs were incapable of generating sufficient force to induce matrix remodeling [96] .…”
Section: Cvd and The Role Of Matrix Stiffnessmentioning
confidence: 92%
See 2 more Smart Citations
“…This is consistent with the notion that aging is a physiological and chronic process attributable to low grade perturbation of multifactorial pathways. A recent study from feed arteries of soleus muscle in rats reported that aged vessels exhibited a decrement in SMC contractility, mainly owing to the impairment of RhoA/ROCK signaling and significant decreased SMα-actin fibers [ 47 ]. This is somewhat inconsistent with our current findings wherein genes encoding both cyto-contractile and contraction regulatory proteins (see GSE145972) were insignificantly attenuated.…”
Section: Discussionmentioning
confidence: 99%